Highly selective C-N and C-S dual functionalization of 1,3-dicarbonyl derivatives using TBHP as an oxidant - Bagad, Pooja K.; Darole, Ratanamala S.; Krishna, G. Rama; Senthilkumar, Beeran (Journal of Organic Chemistry, 2024)
A direct electrosynthesis/photocatalyst-free, atom-economical, and efficient method for the selective synthesis of (E)-3-amino-2-thiocyanato-alpha,beta-unsaturated carbonyl compounds is described through a given protocol. The present approach features the use of inexpensive ammonium thiocyanate to achieve dual functionalization of 1,3-dicarbonyl compounds using TBHP as an oxidant, providing a rapid and practical route to the selective formation of both C-N and C-S bonds via a radical process. This method offers a broad substrate scope with excellent yield and allows for further exploration of the products to construct heterocyclic compounds and other functionalities.